Identification of Schlafen-11 as a Target of CD47 Signaling That Regulates Sensitivity to Ionizing Radiation and Topoisomerase Inhibitors - Kaur, Sukhbir; Schwartz, Anthony L.; Jordan, David G.; Soto-Pantoja, David R.; Kuo, Bethany; Elkahloun, Abdel G.; Mathews Griner, Lesley; Thomas, Craig J.; Ferrer, Marc; Thomas, Anish; Tang, Sai-Wen; Rajapakse, Vinodh N.; et al. (Frontiers in Oncology, 2019)
Knockdown or gene disruption of the ubiquitously expressed cell surface receptor CD47 protects non-malignant cells from genotoxic stress caused by ionizing radiation or cytotoxic chemotherapy but sensitizes tumors in an immune competent host to genotoxic stress. The selective radioprotection of non-malignant cells is mediated in part by enhanced autophagy and protection of anabolic metabolism pathways, but differential H2AX activation kinetics suggested that the DNA damage response is also CD47-dependent. A high throughput screen of drug sensitivities indicated that CD47 expression selectively sensitizes Jurkat T cells to inhibitors of topoisomerases, which are known targets of Schlafen-11 (SLFN11). CD47 mRNA expression positively correlated with schlafen-11 mRNA expression in a subset of human cancers but not the corresponding non-malignant tissues. CD47 mRNA expression was also negatively correlated with SLFN11 promoter methylation in some cancers. CD47 knockdown, gene disruption, or treatment with a CD47 function-blocking antibody decreased SLFN11 expression in Jurkat cells. The CD47 signaling ligand thrombospondin-1 also suppressed schlafen-11 expression in wild type but not CD47-deficient T cells. Re-expressing SLFN11 restored radiosensitivity to a CD47-deficient Jurkat cells. Disruption of CD47 in PC3 prostate cancer cells similarly decreased schlafen-11 expression and was associated with a CD47-dependent decrease in acetylation and increased methylation of histone H3 in the SLFN11 promoter region. The ability of histone deacetylase or topoisomerase inhibitors to induce SLFN11 expression in PC3 cells was lost when CD47 was targeted in these cells. Disrupting CD47 in PC3 cells increased resistance to etoposide but, in contrast to Jurkat cells, not to ionizing radiation. These data identify CD47 as a context-dependent regulator of SLFN11 expression and suggest an approach to improve radiotherapy and chemotherapy responses by combining with CD47-targeted therapeutics.